E-learning Education: Exploring the Impact of Student-Centered E-Learning Education (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Students are exposed to a whole new learning environment while using e-learning, thereforesuccess depends on having various skill sets. Skills in critical thinking, investigation, and assessment arebecoming more and more crucial as students must navigate through expanding amounts of informationfrom many sources. Additionally, students are far more autonomous than in a conventional environment,especially in completely online courses. They must be very focused and dedicated to teaching, with littlesocial contact with students or the teacher. Although there is a greater rate of withdrawals or incompletegrades in online courses, students generally do as well as in traditional classroom settings. E-learning is apedagogy for student-centered and collaborative learning that may be thought of as both computerassistedlearning and pedagogy. Early innovations in e-learning centred on computer-assisted learning,when some or all of the learning materials are sent digitally. The educational component of e-learninghas gained prominence more lately. All modes of learning and teaching that are facilitated electronicallyfall under the category of e-learning. Whether or whether networked learning is used, information andcommunication technologies act as particular medium to carry out the learning process.